(untitled) (Revista Brasileira de Contabilidade e Gestão, 2016)
This study aims to map the scientific production of events ANPCONT, Congress USP-CC, and BCC ENANPAD, on the theme of intangible assets in the course of all editions held events surveyed in order to outline the methodological characteristics of articles and analyze how the works are distributed, according to the years, the events with respect to the development of the theme. The survey ranks the aims, descriptive, with design and collection of bibliographic data, the nature and technique of data analysis is classified as quantitative and qualitative. The findings show a total of 16,607 articles, with 133 of these works that deal with the subject. The Brazilian Congress of costs showed the greatest volume of articles, but was ANPCONT with the highest percentage of work on the issue when comparing the numbers of items related by Congress. The most productive years were the theme of the 2004, 2005 and 2007 and coincided with the disclosure of important standards for the subject, both national and international level. The decrease of publications since 2010 may reflect the relationship of the subject with convergence of Brazilian standards with international accounting. Methodologically, were high rates of jobs that do not clearly exposed their methodologies, but among the more obvious highlights the descriptive literature, indirect and qualitative research documentary.